Modeling Thermal Suitability for Reindeer (Rangifer tarandus ssp.) Brainworm (Elaphostrongylus rangiferi) Transmission in Fennoscandia - Rose Vineer, Hannah; Mørk, Torill; Williams, Diana J.; Davidson, Rebecca K. (Frontiers in Veterinary Science, 2021)
The brainworm, Elaphostrongylus rangiferi, is a nematode which causes neurological disorders (elaphostrongylosis) in reindeer (Rangifer tarandus ssp.). Favourable climatic conditions have been inferred as the cause of sporadic outbreaks of elaphostrongylosis in Norway, supported by positive associations between observed outbreaks/intensity of infection and summer temperatures in the previous years. Climate warming which results in increased transmission of E. rangiferi therefore presents a risk to the health of semi-domesticated and wild reindeer in Fennoscandia (Norway, Sweden and Finland), the health of co-grazing small ruminants, and the livelihoods of indigenous Sámi herders. As a first step towards developing climate change impact assessments for E. rangiferi, a degree-day model was developed for larval development in a range of gastropod hosts and applied to historic weather data. Predictions were validated by statistical and qualitative comparison against historic parasitological and outbreak records. The model predicted an overall increase in thermal suitability for E. rangiferi, which was statistically significant in the north and along the Scandinavian mountain ranges, where reindeer density is highest. In these regions annual cumulative temperature conditions are suitable for larval development within a single year, potentially changing E. rangiferi epidemiology from a 2-year transmission cycle to a 1-year transmission cycle. This is the first mechanistic model developed for E. rangiferi and could be used to inform veterinary risk assessments on a broad spatial scale. Limitations and further developments are discussed.